ENGLISH FOR MARITIME - Lucia Tri Natalia Sudarmo; Heidy Wulandari; Marita Safitri; Fransiscus Widya Kiswara (Bandar Lampung University (UBL), 2016)
English education in Indonesia vocational schools are in the need of specific curriculum for each kind of vocational school. This study is a response toward a vocational English teacher experience, in which English lesson in maritime school still applies general English and even English for hotel during the learning process. It aims to provide materials which have direct relation to navigation in maritime school. The products of this study are syllabus and a module entitled English for Maritime consisting of thirteen units which is expected to be used by students of SMK Pelayaran Kupang. Research and development (R&D) method is applied in designing the materials.